AB1150 Health related quality of life in patients with juvenile idiopathic arthritis. (23rd January 2014) - Susic, G.; Stojanovic, R.; Soldatovic, I.
Abstract : Background: Juvenile idiopathic arthritis (JIA) as a chronic disease, has a major impact not only on physical ability, but also on emotional and social aspect of patient's life. Objectives: To assess health related quality of life (HRQL) of patients with JIA and ability of Childhood Health Questionnaire (CHQ) in predicting outcome of the disease. Methods: Patients were examined clinical and laboratory at the beginning and after 2-5, 24 yrs.; parents completed CHQ – generic self-administered instrument designed to capture physical, emotional and social components of health status. In addition there 2 summary measures based on US normative standard: physical score (PhS) and psychosocial score (PsS) was calculated (50±10) [1]. Higher scores in the scales indicate better HRQL. Poor HRQL was defined by PhS or PsS <30, means <2 SD below normal for healthy children.Patients were classified according to outcome status (active or remission) using criteria Wallace et al. [2]. To determine predictive value of CHQ regression models were used. Results: The study included 87 pts. (f 69%, m 31%) median age 14 yrs., median disease duration 4 yrs. (range 2, 0-18, 0). PhS and PsS showed improvement at the last visit (37, 01 vs. 44, 66, 48, 44 vs. 53, 76; p<0, 001); number of patients with PhS<2 SD decreased (20, 2% vs. 10, 1% pts., p<0, 05). PhS was significantly lower in patients with active disease compared to patients in remission on/without medications. (38, 12 vs. 48, 29 vs. 52, 47, p<0, 01). PhS CHQ significantly correlated with the majority of clinical and laboratory parameters of disease activity (p<0, 001), PGA and parent's/patient's assessment (p<0, 001), disease damage index at the end of a follow-up (p<0, 01). The similar findings were observed at baseline. PsS demonstrated weak correlation only with PGA (p<0, 05) and parent's/patient's assessment of well/being (p<0, 01). PhS showed good predictive ability when it was compared on baseline with outcome at the last examination (p<0, 001), but PsS didn't demonstrated significant ability in predicting outcome of the disease. Odds ratio for patients with PhS<30 at the baseline was 6, 4 (CI=1, 837-22, 415, p=0, 01), compared to patients with PhS>30. Using Cox regression analysis and taking into account the time interval between two examinations hazard ratio for patients with poor HRQL was 2, 2 (CI=1, 103 - 4, 475, p<0, 05) compared to patients with PhS>30. Conclusions: HRQL of patients with JIA was significantly improved during the follow-up period, which could be addressed to efficacy of treatment. Physical aspect of HRQL more that psychosocial, is largely influenced by activity of the disease and severity as well. CHQ is useful tool in predicting outcome and identifying the patients with poor prognosis. References: Ruperto N. et al. Clin Exp Rheumatol 2001; 19 (suppl.23):S1-S9. Wallace CA et al. J Rheumatol 2004;31:2290-94. Disclosure of Interest: None Declared